A new species of Trombidium (Acari: Trombidiidae) from East Azarbaijan province, Iran - Saboori, Alireza; Irani-Nejad, Karim Haddad (Zootaxa, 2007)
A new species of larval Trombidium, collected as free-living on soil, is described and illustrated from Tickmadash, Mianeh City, East Azarbaijan province, Iran. This is the second species of Trombidium from Iran. A key to Iranian genera of Trombidiidae (larva) is presented.